Pemasaran dan tingkat pendapatan usaha ikan asap Di Desa Wasori Kecamatan Biak Timur Kabupaten Biak Numfor Provinsi Papua - Rumere, Mira Solita D; Nurdiana A; Piliana, Wa Ode; Ishak, Ermayanti; Haslianti; Sriwulan, Desy (Universitas Halu Oleo, 2023)
Smoked fish processing is one of the livelihoods of the people in Biak Numfor Regency, but its marketing efficiency is not yet known. This study aims to determine the process of processing smoked fish, margins, marketing efficiency and income obtained by smoked fish business processors in Wasori Village, East Biak District, Biak Numfor Regency, Papua. This study was carried out in January-February 2022. The determination of respondents for smoked fish processors was carried out using the census method with 9 respondents and the determination of retailers was carried out using purposive sampling with the 3 retailers. Data were obtained through interviews using structured questionnaires. The data analysis used was a quantitative descriptive analysis using data on marketing margins, marketing efficiency and revenue. The results showed that there were three types of fish that were processed into smoked fish, namely skipjack tuna (Katsuwonus Pelamis), chicken fish (Abalistes Stellaris) and snapper (Lutjanidae). There were two channels for marketing smoked fish, namely channel I of processing smoked fish was sold directly to consumers and channel II processing of smoked fish was sold to retailers and then to consumers. The average marketing margin in channel II for skipjack tuna was IDR 10,000, chicken fish was IDR 10,000 and snapper was IDR 5,000. The most efficient marketing channels were in channel I for skipjack tuna, which was 25.71%, chicken fish was 22.5% and the snapper was 18.94%. Meanwhile, channel II was less efficient because it obtained a value of 34.67% for skipjack tuna, chicken fish was 36.59% and snapper was 26%. The smoked fish business earned an average total income of IDR 22,366,153 / month with the highest average total income of IDR 28,563,500 / month and the lowest average total income of IDR 17,134,750 / month. This research showed that the smoked fish business in Wasori Village is efficient and very profitable.